Touchomatic: interpersonal touch gaming in the wild - Marshall, Joe; Tennent, Paul (2017)
Direct touch between people is a key element of social behaviour. Recently a number of researchers have explored games which sense aspects of such interpersonal touch to control interaction with a multiplayer computer game. In this paper, we describe a long term, in-the-wild study of a two-player arcade game which is controlled by gentle touching between the body parts of two players. We ran the game in a public videogame arcade for a year, and present a thematic analysis of 27 hours of gameplay session videos, organized under three top level themes: control of the system, interpersonal interaction within the game, and social interaction around the game. In addition, we provide a quantitative analysis of observed demographic differences in interpersonal touch behaviour. Finally, we use these results to present four design recommendations for use of interpersonal touch in games.